Heavy metal concentrations in soils, vegetation, earthworms and wood mice from Heteren and Plateaux, The Netherlands - Nico W Van Den Brink; Dennis Lammertsma; Wim Dimmers; Marie-Claire Boerwinkel; Annemariet van der Hout (PANGAEA, 2010)
Effects of soil properties on the accumulation of metals to wood mice (Apodemus sylvaticus) were evaluated at two sites with different pH and organic matter content of the soil. pH and organic matter content significantly affected accumulation of Cd, Cu, Pb and Zn in earthworms and vegetation. For Cd, Cu and Zn these effects propagated through the food web to the wood mouse. Soil-to-kidney ratios differed between sites: Cd: 0.15 versus 3.52, Cu: 0.37 versus 1.30 and Zn: 0.33-0.83. This was confirmed in model calculations for Cd and Zn. Results indicate that total soil concentrations may be unsuitable indicators for risks that metals pose to wildlife. Furthermore, environmental managers may, unintentionally, change soil properties while taking specific environmental measures. In this way they may affect risks of metals to wildlife, even without changes in total soil concentrations.
Supplement to: Van Den Brink, NW et al. (2010): Effects of soil properties on food web accumulation of heavy metals to the wood mouse (Apodemus sylvaticus). Environmental Pollution, 158(1), 245-251, https://doi.org/10.1016/j.envpol.2009.07.013